2013
DOI: 10.1371/journal.pone.0076064
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Intraovum Transmission of a Microsporidium of Vertebrates: Pseudoloma neurophilia Infecting the Zebrafish, Danio rerio

Abstract: Direct transmission from parents to offspring, referred to as vertical transmission, occurs within essentially all major groups of pathogens. Several microsporidia (Phylum Microsporidia) that infect arthropods employ this mode of transmission, and various lines of evidence have suggested this might occur with certain fish microsporidia. The microsporidium, Pseudoloma neurophilia, is a common pathogen of the laboratory zebrafish, Danio rerio. We previously verified that this parasite is easily transmitted horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 44 publications
1
55
0
Order By: Relevance
“…17 Infection by P. hyphessobryconis often results in clinical signs such as grossly visible lesions and high levels of mortality. In contrast, infections by P. neurophilia are often subclinical and the ability for this parasite to be transmitted vertically within the developing embryo, 18 at least in D. rerio, provides another route leading to the persistence of this parasite in both laboratory colonies and pet stores.…”
Section: Discussionmentioning
confidence: 99%
“…17 Infection by P. hyphessobryconis often results in clinical signs such as grossly visible lesions and high levels of mortality. In contrast, infections by P. neurophilia are often subclinical and the ability for this parasite to be transmitted vertically within the developing embryo, 18 at least in D. rerio, provides another route leading to the persistence of this parasite in both laboratory colonies and pet stores.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not know whether infected eggs would have developed into fry or whether those fish would have developed infections. It is notable that in 2 other fish-infecting microsporidia (Ovipleistophora ovariae and Pseudoloma neurophilia), initial molecular and observational evidence for vertical transmission were doubted, but more sophisticated techniques confirmed that these parasites are vertically transmitted (Phelps & Goodwin 2008, Sanders et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as previously discussed, 9,12 these methods contribute to good biosecurity and, as such, are likely to reduce the spread of microorganisms. However, they are less likely to prevent the spread of intraovum pathogens (e.g., Pseudoloma neurophilia) 23 and a holistic approach, including additional disease prevention and control measures, should be taken in addition to embryo disinfection.…”
Section: Figmentioning
confidence: 99%